Atentados y política: asesinato del General Schneider y su impacto en la prensa española - Díaz Aguad, Alfonso (2024)
This paper aims to identify the reactions that the assassination of General René Schneider, which took place in Chile in 1970, provoked in the Spanish press of the time. Based on a historiographic analysis of newspaper sources, periodicals were reviewed, considering their circulation criteria, national projection and relationship with a political tendency. In this descriptive review of sources, it was possible to identify that the way of approaching this evento was influenced by their editorial lines.